2018
DOI: 10.3389/fmicb.2018.00513
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Dependent Iron Oxidation: A Potential Mars Metabolism

Abstract: This work considers the hypothetical viability of microbial nitrate-dependent Fe2+ oxidation (NDFO) for supporting simple life in the context of the early Mars environment. This draws on knowledge built up over several decades of remote and in situ observation, as well as recent discoveries that have shaped current understanding of early Mars. Our current understanding is that certain early martian environments fulfill several of the key requirements for microbes with NDFO metabolism. First, abundant Fe2+ has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 186 publications
(270 reference statements)
3
36
0
Order By: Relevance
“…For example, this occurs in marine sediments and hydrothermal vents, where there is limited light and a gradient in the availability of oxygen and nitrate 86,87 , and in artificial environments, such as wastewater treatment plants, which have higher concentrations of nitrate 88,89 . On Mars, the oxidation of sulfur species could be coupled to these electron acceptors in a similar manner 90 . For example, oxygen has been detected in the martian atmosphere by the Curiosity rover 25 , with thermodynamic models indicating that subsurface environments on Mars could possess sufficient O 2 to allow for aerobic metabolisms to be viable 67 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, this occurs in marine sediments and hydrothermal vents, where there is limited light and a gradient in the availability of oxygen and nitrate 86,87 , and in artificial environments, such as wastewater treatment plants, which have higher concentrations of nitrate 88,89 . On Mars, the oxidation of sulfur species could be coupled to these electron acceptors in a similar manner 90 . For example, oxygen has been detected in the martian atmosphere by the Curiosity rover 25 , with thermodynamic models indicating that subsurface environments on Mars could possess sufficient O 2 to allow for aerobic metabolisms to be viable 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic ammonium oxidation coupled to Fe(III) reduction (Feammox) 16 has been found in soils but not yet the ocean. Nitrate oxidation of Fe(II) has also been considered as possibly supporting life on Mars 17 . The balance between microbial and abiotic oxidation rates for Fe(II) has implications for both our present day understanding of Fe cycling and that of the past 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are a complex (eukaryotic) form of life that appeared relatively late in Earth history . Organisms sustained by lithoautotrophic metabolic strategies plausible for hypothetical life on Mars (e.g., methanogenesis; nitrate‐dependent iron oxidation) are abundant in Earth's deep biosphere, but it has not been demonstrated that any of the candidate fossils from the deep biosphere represent such organisms, although some rather unusual examples might conceivably do so . More work is needed, in particular, to search for and characterize definitively prokaryotic fossil remains from the basalt‐hosted deep biosphere.…”
Section: Major Challenges For Subsurface Palaeobiologymentioning
confidence: 99%